In situ investigation on densification mechanism of Ti-20Al-19Nb (at.%) alloy by TiH2-assisted pressureless sintering - Cai, Qi; Yu, Qilin; Li, Xinyao; Lu, Yao; Li, Yanmo; Cui, Ganggang (Elsevier, 2023)
Dense Ti-20Al-19Nb (at.%) alloys can be cost-effectively fabricated by TiH2-assisted pressureless sintering; nevertheless, the densification mechanism remains controversial without understanding the entire sintering process. By in situ observing the surface morphology of the Ti/Al/Nb and Ti/TiH2/Al/Nb compacts upon heating, the densification mechanism of the Ti-20Al-19Nb alloys was elucidated in this study. In addition to the reported reason that the dehydrogenation of TiH2 provided reactive Ti, the densification of Ti-20Al-19Nb alloy was found to be strongly associated with the phase transformations upon sintering. The TiH2 participated in the reverse eutectoid transformation, α-Ti + δ-TiH2 → β-Ti, inducing the α/β and TiH2/β grain boundaries for the rapid diffusion of Al. The reaction of Ti(s) + Al(s) → TiAl3(s) was then accelerated, and the majority of the Al phase was consumed in the solid state, which significantly reduced the pores from the transient liquid Al. The activation energy of the Ti-Al reaction decreased with the addition of TiH2, and the growth mode of the TiAl3 phase was changed. By removing the large pores at 700 °C, the Ti-Al intermetallic phases were well connected, forming the continuous interdiffusion route for Ti, Al, and Nb. The diffusion of Nb, as well as the phase transformation of α2 → B2, was then promoted, and the ripening time for the B2 phase was increased. As a result, the density and mechanical properties were improved. The initial results of this study provided a foundation for the cost-effective fabrication of high-strength Ti-Al alloys containing refractory elements.
Keywords: Ti-Al-Nb alloy; Sintering mechanism; Porosity; In situ observation; Phase transformation